Electrospun cellulose acetate butyrate/polyethylene glycol (CAB/PEG) composite nanofibers: A potential scaffold for tissue engineering - Tan, Hui Li; Kai, Dan; Pasbakhsh, Pooria; Teow, Sin Yeang *; Lim, Yau Yan; Pushpamalar, Janarthanan (Elsevier, 2020)
Electrospinning is a common method to prepare nanofiber scaffolds for tissue engineering. One of the common cellulose esters, cellulose acetate butyrate (CAB), has been electrospun into nanofibers and studied. However, the intrinsic hydrophobicity of CAB limits its application in tissue engineering as it retards cell adhesion. In this study, the properties of CAB nanofibers were improved by fabricating the composite nanofibers made of CAB and hydrophilic polyethylene glycol (PEG). Different ratios of CAB to PEG were tested and only the ratio of 2:1 resulted in smooth and bead-free nanofibers. The tensile test results show that CAB/PEG composite nanofibers have 2-fold higher tensile strength than pure CAB nanofibers. The hydrophobicity of the composite nanofibers was also reduced based on the water contact angle analysis. As the hydrophilicity increases, the swelling ability of the composite nanofiber increases by 2-fold with more rapid biodegradation. The biocompatibility of the nanofibers was tested with normal human dermal fibroblasts (NHDF). The cell viability assay results revealed that the nanofibers are non-toxic. In addition to that, CAB/PEG nanofibers have better cell attachment compared to pure CAB nanofibers. Based on this study, CAB/PEG composite nanofibers could potentially be used as a nanofiber scaffold for applications in tissue engineering.